Study of Thermal Activated CO2 Extraction Processes from Carbonate Apatites Using Gas Chromatography - V.N. Kuznetsov; A.A. Yanovska; S.V. Novikov; V.V. Starikov; T.G. Kalinichenko; A.V. Kochenko; A.G. Ryabyshev; Ya.V. Khyzhnya; S.N. Danilchenko (Журнал нано- та електронної фізики)
The study of carbonate in the structure of carbonate-containing apatites (CCA) is an actual problem due to the similarity of such systems to natural apatites of mammalian bone tissue. The search of the optimal synthesis procedures was also carried out in order to obtain carbonate apatites with the highest rate of carbonate ions incorporation into the apatite structure. The analysis of carbonate-group temperature behavior in apatites of various origin helps to understand their structural and functional roles in biologically relevant apatite materials. The thermal extraction and accumulation of CO2 from biogenic and geological apatites is also of interest for the further carbon isotope analysis with accelerating mass-spectrometry. X-ray diffraction analysis, infrared spectroscopy and scanning electron microscopy as well as self-proposed gas chromatography method with thermo-programmed probe extraction were used for carbonate temperature behavior study. This new method allows determining CO2 concentration released from CCA during annealing. The defined changes in carbonate apatite structure depending on synthesis procedure were observed.